Instruction time and student achievement: The moderating role of teacher qualifications - Katharina Wedel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Recent evidence suggests a positive effect of the quantity of instruction on student achievement. In this paper, I focus on the interaction between the quantity and the quality of instruction. Using international TIMSS data, I exploit within-student between-subject variation. I find that on average, an additional hour of instruction time leads to an increase of 0.03 standard deviations in students' test scores across all countries. Importantly, these effects of instruction time are significantly larger for students with better qualified teachers, resulting in an increase in test scores of 0.04 to 0.05 standard deviations. While on average, instruction time has no significant effect in developing countries, it increases test scores by 0.02 standard deviations when taught by a high-qualified teacher also in developing countries.
Keywords: I21; I25; C21; 330; Instruction time; student achievement; teacher qualifications; education production function; TIMSS